Znaczenie środków pomocowych Unii Europejskiej w rozwoju sektora MŚP - Starzyńska, Wacława (SME Sector and Financial Support of the European Union. The Case Study, 2007)
Small and medium enterprises (SMEs) are a very important sector of national economy. They are the main source of jobs and create high percentage of GDP, on the other hand. Although main macro indicators of the SME sector in Poland in principle are similar to the European ones, the Polish SMEs are weaker than the EU enterprises in terms of personal, capital, and technical conditions. High percentage of analyzed firms in Poland are characterized by low ability of taking an economic risk under investment process because they base only on own financial means. During a recession such means are very poor. But if SMEs decide to use external financial sources they often are not able to manage their liability risk. The paper aims at the role of the EU Programme SAPARD in restructuring food industry and marketing improving of agricultural products taking as an example a co-operative of milk processing industry. The co-operative investment of about 5 mln zloty of value was financed in 50 percent by the SAPARD Programme means. However, the financial support may not be available until the investments are completely finished. The paper tries to measure the impact of new investment of analyzed enterprise supported by the EU programme on the enterprise financial results
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 507-517